Pyro-Electrification of Freestanding Polymer Sheets: A New Tool for Cation-Free Manipulation of Cell Adhesion in vitro - Rega, Romina; Gennari, Oriella; Mecozzi, Laura; Pagliarulo, Vito; Mugnano, Martina; Oleandro, Emilia; Nazzaro, Filomena; Ferraro, Pietro; Grilli, Simonetta (Frontiers in Chemistry, 2019)
Localized electric fields have become, in recent years, a source of inspiration to researchers and laboratories thanks to a huge amount of applications derived from it, including positioning of microparticles as building blocks for electrical, optical and magnetic devices. The possibility of producing polymeric materials with surface charge, thus opening new perspectives for applications where process simplicity and cost-effectiveness of flexible electronics are of fundamental importance. In particular, the influence of surface charges is widely studied and is a critical issue especially when new materials and functional technologies are introduced. Here, we report a voltage-free pyro-electrification (PE) process able to induce a permanent dipole orientation into polymer sheets under both mono- and bi-polar distribution. The technique makes use of the pyroelectric effect for generating electric potentials in the order of kV by an easy to accomplish thermal treatment of ferroelectric lithium niobate (LN) crystals. The PE allows us to avoid the expensive and time-consuming fabrication of high power electrical circuits, as occurs in traditional generator-based techniques. Since the technique is fully compatible with spin coating-based procedures the pyro-electrified polymer sheets are easily peeled off the surface of the LN crystal after PE completion, thus providing highly stable and freestanding charged sheets. We show the reliability of the technique for different polymers and for different applications ranging from live cell patterning to biofilm formation tests for bacteria linked to food-processing environments.